Bi-stable composite panels - Pow, Joel Wei Wei. (2013)
Bi-stable composites have interested researchers in the aviation industry for quite some time now due to its ability to exist in two stable configurations. It fuels the possibility of a morphing wing which could alter its wing profile to suit operational requirements without the use of heavy actuators. Bi-stable composites are able to display two stable configurations as a result of induced residual stresses as it cools down from its curing temperature. In this report, the fundamental structural responses of unsymmetrical cross-ply laminates were observed over a period of time. Rectangular cross-ply laminates of the stacking sequence [0n/90n]T were fabricated and its curvatures and critical snap-through load were observed over a period of time. It was found that the curvatures and critical snap-through load decreases over time and these laminates will eventually lose its bi-stability. The amount of influence that moisture have on the rate of bi-stability loss was also investigated upon but its results were rather inconclusive. The gradual loss of bi-stability may deem unsymmetrical cross-ply laminates unsuitable to be used in a morphing wing unless there is a solution to prevent its properties from changing with time. A viable solution may be to use other types of bi-stable composites such as the pre-stressed symmetrical laminates, which have been claimed to be unaffected by temperature and moisture.